Penggunaan Media Pembelajaran Media Bahan Bekas dalam Mengembangkan Kemampuan Musikal Anak Usia Dini - Andi Iting; Hasriani Hasriani (JURNAL MAPPESONA, 2025)
This research discusses the use of recycled materials as learning media in developing children's musical abilities at Mamminasae Kindergarten, located in Bulu-bulu Village, Tonra Subdistrict, Bone Regency. The objectives of this study are: (1) to identify the use of recycled material-based learning media at Mamminasae Kindergarten, and (2) to examine how this media contributes to the development of children's musical abilities. To obtain the data, the researcher employed a qualitative research method with descriptive analysis. The data collection techniques used in this study include observation, interviews, and documentation. Based on the research findings at Mamminasae Kindergarten, the study concludes that the use of recycled material-based learning media follows several stages. In the planning stage, teachers are required to design learning activities that align with the students’ needs. In the implementation stage, teachers explain to the children how to create learning media using recycled materials. In the final stage, teachers evaluate the media created by the students. The use of recycled material-based learning media at Mamminasae Kindergarten has proven to support the development of children's musical abilities. This is evident from the children’s progress; before using recycled materials as musical instruments, the children were hesitant and unable to recognize musical notes properly. Even singing posed significant difficulty. However, after the implementation of recycled material-based media, the children began to demonstrate noticeable improvements in their musical skills.